2014
DOI: 10.1017/jfm.2014.475
|View full text |Cite
|
Sign up to set email alerts
|

Pressure fluctuations beneath instability wavepackets and turbulent spots in a hypersonic boundary layer

Abstract: To investigate the pressure-fluctuation field beneath turbulent spots in a hypersonic boundary layer, a study was conducted on the nozzle wall of the Boeing/AFOSR Mach-6 Quiet Tunnel. Controlled disturbances were created by pulsed-glow perturbations based on the electrical breakdown of air. Under quiet-flow conditions, the nozzle-wall boundary layer remains laminar and grows very thick over the long nozzle length. This allows the development of large disturbances that can be well-resolved with high-frequency p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
39
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 52 publications
12
39
2
2
Order By: Relevance
“…After being first observed in DNS, these structures have now also been observed in laboratory experiments by Casper et al (2014). With respect to the part of the growth mechanism that was affected by compressibility, Redford et al (2012) showed how it was the destabilisation of the surrounding boundary layer (Gad-El-Hak's second mechanism) that was affected by Mach number, with a much slower rate of generation of new structures at Mach 6 compared to Mach 3 in their simulations.…”
Section: Turbulent Spotsmentioning
confidence: 77%
“…After being first observed in DNS, these structures have now also been observed in laboratory experiments by Casper et al (2014). With respect to the part of the growth mechanism that was affected by compressibility, Redford et al (2012) showed how it was the destabilisation of the surrounding boundary layer (Gad-El-Hak's second mechanism) that was affected by Mach number, with a much slower rate of generation of new structures at Mach 6 compared to Mach 3 in their simulations.…”
Section: Turbulent Spotsmentioning
confidence: 77%
“…Experimental work comparing the linear growth of second mode with the results of the linear stability theory (LST) has been undertaken both in quiet [12,15,16] and noisy tunnels [13,17,18]. The nonlinear stages of the second-mode evolution and its relevance to turbulence development was investigated both by direct numerical simulations (DNS) [19][20][21][22][23] and experiments [24][25][26][27]. Issues related to the effect of the surface roughness have also been discussed [28][29][30].…”
Section: A Second-mode Instabilitymentioning
confidence: 99%
“…For relatively sharp bodies at hypersonic speeds in particular, the transition is dominated by second-mode waves, or fast-slow modes [3], which are manifest as convectively amplified streamwise-propagating disturbances with a distinctive acoustic signature, typically in the ultrasonic range. Many numerical [4][5][6][7][8][9][10] and experimental [11][12][13][14][15][16][17][18][19][20] works have confirmed the existence of such instabilities.…”
mentioning
confidence: 99%